THE Terrestrial Mammal Species Diversity in The Lamandau Wildlife Reserve Central Kalimantan Province - Fauzi, Fouad; Erawati; Mohamad Rizal; Nisfiatul Hidayat; Milad Madiyawati (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2025)
The aim of this research is to inventory the diversity of land mammal species in the Lamandau Wildlife Reserve, Central Kalimantan Province. The method used is direct and indirect observation using strip transects and camera traps. The research results obtained ten types of mammals at three different observation sites, namely Gemini camp, JL camp and Rasak camp. The calculation results show that the richness index (R) and diversity index (H') of each camp are relatively low, while the evenness index (E) of each camp is relatively high.